America is in the heart Ilocano immigration to the United States, 1906-1930 - Foronda, Jr., Marcelino A. (1976)
The immigration of Filipinos - and that includes Ilokanos - to Hawaii and mainland United States from 1906, when they first began to arrive in appreciable numbers, to 1930, when the depression somewhat halted the influx of Filipinos, may not be termed "immigration" in the general accepted sense of the term, for during that time, the Philippines was still under American colonial rule, and as such the Filipinos were considered as American nationals. This paper attempts to describe the trends in Ilocano immigration to the United States from 1906-1930.